2016
DOI: 10.1016/j.amjcard.2016.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Anxiety as a Risk Factor for Cardiovascular Disease

Abstract: Whether anxiety is a risk factor for a range of cardiovascular diseases is unclear. We aimed to determine the association between anxiety and a range of cardiovascular diseases. MEDLINE and EMBASE were searched for cohort studies that included participants with and without anxiety, including subjects with anxiety, worry, posttraumatic stress disorder, phobic anxiety, and panic disorder. We examined the association of anxiety with cardiovascular mortality, major cardiovascular events (defined as the composite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
138
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(154 citation statements)
references
References 50 publications
6
138
1
9
Order By: Relevance
“…The inverse association of anxiety with stroke is likely a spurious finding because of the comparatively small number of strokes. Prior cohort studies demonstrated an increased stroke risk in individuals with anxiety 20. In patients with AF, anxiety may be related to better compliance and medication adherence, however we could not demonstrate clear evidence to prove these assumption in our data.…”
Section: Discussioncontrasting
confidence: 82%
“…The inverse association of anxiety with stroke is likely a spurious finding because of the comparatively small number of strokes. Prior cohort studies demonstrated an increased stroke risk in individuals with anxiety 20. In patients with AF, anxiety may be related to better compliance and medication adherence, however we could not demonstrate clear evidence to prove these assumption in our data.…”
Section: Discussioncontrasting
confidence: 82%
“…For example, it is well established that anxiety is associated with several chronic physical co-morbidities [1]. Of particular concern are cardiovascular diseases [8], diabetes [9], pulmonary diseases [10], chronic pain [11], infectious diseases such as tuberculosis [12], arthritis [13], edentulism [14], and mainly in older people, visual impairment [15] and hearing problems [16]. Given the increasing prevalence of chronic conditions worldwide [17], a further understanding of the determinants, consequences and management of the comorbidity between anxiety and chronic physical conditions should be a research priority.…”
Section: Introductionmentioning
confidence: 99%
“…Približno 50 % bolnikov s koronarno boleznijo ima tudi depresivnost in anksioznost (8). Pri anksioznih bolnikih je tveganje za koronarno bolezen za 26 % višje, za 48 % višje pa je tveganje za srčno smrt (9,10). Bolniki s hudimi simptomi depresivnosti in anksioznostjo so imeli najvišjo prevalenco koronarne bolezni (11).…”
Section: Uvodunclassified